2019
DOI: 10.2147/copd.s210916
|View full text |Cite
|
Sign up to set email alerts
|

<p>End-of-life care in individuals with respiratory diseases: a population study comparing the dying experience between those with chronic obstructive pulmonary disease and lung cancer</p>

Abstract: Purpose Among individuals with COPD and/or lung cancer, to describe end-of-life health service utilization, costs, and place of death; to identify predictors of home palliative care use, and to assess benefits associated with palliative care use. Patients and methods We conducted a retrospective population-based study using provincial linked health administrative data (Ontario, Canada) between 2010 and 2015. We examined health care use in the last 90 days of life in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
2
22
1
2
Order By: Relevance
“…2628 Two studies compared a population with COPD to a population with both lung cancer and co-existing COPD with one retrospective 29 and one prospective design. 30 Three studies 10,31,32 compared across three disease groups: COPD, lung cancer, both COPD and lung cancer. All three studies were retrospective and utilized health administrative data.…”
Section: Resultsmentioning
confidence: 99%
“…2628 Two studies compared a population with COPD to a population with both lung cancer and co-existing COPD with one retrospective 29 and one prospective design. 30 Three studies 10,31,32 compared across three disease groups: COPD, lung cancer, both COPD and lung cancer. All three studies were retrospective and utilized health administrative data.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the effectiveness of SPC for symptom control and generalized support [ 16 ] and the documented positive outcomes for patients with COPD [ 17 ], it is reasonable to assume that both LC and COPD patients would be candidates for SPC. Butler et al recently reviewed comparative studies on COPD and LC [ 4 ], however, 10 of the 20 studies reviewed were based on data collected more than 10 years earlier and, among the more recent studies, only two included 1000 or more patients [ 18 , 19 ]. For this reason, we aimed to conduct a large study using recent data, as inclusion criteria for admission to palliative care services for non-malignant conditions such as COPD are changing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Despite availability of staging criteria, it is not always clear when someone with COPD is approaching EOL (Braço Forte & Sousa, 2017 ). Further, people with end stage COPD are far less likely to obtain palliative care than people with the same symptoms and illness profile with lung cancer (Butler et al, 2020 ; Kendzerska et al, 2019 ). Over the past decade, there has been increased recognition that health professionals need to develop better approaches for management of people suffering from advanced COPD.…”
Section: The Copd Experiencementioning
confidence: 99%
“…A deeper understanding of the experiences of people with COPD and their family caregivers can lead to better EOL care, which is especially important given the limited resources for non-cancer related EOL care (Lilly & Senderovich, 2016 ). In one population-based study in Ontario, Canada, people with COPD were found to be far less likely to receive palliative care than a sample of people with lung cancer (Kendzerska et al, 2019 ). The researchers found palliative care to be associated with fewer deaths in the acute care setting, fewer days in acute care, and less cost, regardless of whether the diagnosis was lung cancer or COPD (Kendzerska et al, 2019 ).…”
Section: The Copd Experiencementioning
confidence: 99%
See 1 more Smart Citation